2019
DOI: 10.1016/j.cjtee.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the skull base fracture and the incidence of intracranial hemorrhage in patients with traumatic brain injury

Abstract: PurposeA head injury (HI) may cause a skull fracture, which may or may not be associated with injury to the brain. In essence, a skull base fracture (SBF) is a linear fracture at the base of the skull. Loss of consciousness and Glasgow coma score (GCS) may vary depending on an associated intracranial pathology. The pathomechanism is believed to be caused by high energy impact directly to the mastoid and supraorbital bone or indirectly from the cranial vault. Aim of this study is to define the correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 7 publications
0
9
0
2
Order By: Relevance
“…In addition, blunt trauma is accountable for over 90% of all SBF's [ 12 ], with most injuries located in the anterior fossa (51%) [ 13 ]. Faried et al, reported on the occurrence of around 69.4% of cases in the anterior fossa, while 27.5% was in the middle cranial fossa [ 14 ]. Mokolane et al described the center area as the most common target point, and is assumed as the weakest area, due to the presence of neurovascular foramina and thin bones [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, blunt trauma is accountable for over 90% of all SBF's [ 12 ], with most injuries located in the anterior fossa (51%) [ 13 ]. Faried et al, reported on the occurrence of around 69.4% of cases in the anterior fossa, while 27.5% was in the middle cranial fossa [ 14 ]. Mokolane et al described the center area as the most common target point, and is assumed as the weakest area, due to the presence of neurovascular foramina and thin bones [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sebagian besar pemeriksaan neurologis memberikan hasil normal, keparahan MHI berhubungan dengan gejala klinis. MHI dapat menyebabkan fraktur, intracranial hemorrhage (ICH), hemorrhagic stroke dan ischemic stroke pada daerah ganglia basalis [11][12][13][14] .Cedera kepala telah dikategorikan : ringan, sedang dan berat sesuai dengan tingkat keparahan oleh Glasgow Outcome Scale (GCS [15]. Selain itu, Cranial malformations dan head congenital menunjukkan pencitraan CT mampu mendeteksi dengan baik [16].…”
Section: Pendahuluanunclassified
“…Due to the close relationship among tympanum, inner ear, acoustical ossicle and auditory nerve, especially the anatomical location of the middle skull base, hearing impairment is more common in fractures of the middle skull base. 1 Hearing impairment after trauma can be divided into auditory nerve injury and non-neurological injury according to the pathogenesis. The main causes of non-neurological injury include tympanic membrane damage, tympanic effusion and acoustical ossicle fracture, etc.…”
Section: Introductionmentioning
confidence: 99%